A critical appraisal of evidence-and consensus-based guidelines for actinic keratosis - Wessely, Anja; Steeb, Theresa; Heppt, Franz; Hornung, Annkathrin; Kaufmann, Matthias; Koch, Elias; Toussaint, Frédéric; Erdmann, Michael; Berking, Carola; Heppt, Markus (Current Oncology, 2021)
Actinic keratoses (AK) are common lesions of the skin that can be effectively treated with several lesion-and field-directed treatments. Clinical practice guidelines assist physicians in choosing the appropriate treatment options for their patients. Here, we aimed to systematically identify and evaluate the methodological quality of currently available guidelines for AK. Guidelines published within the last 5 years were identified in a systematic search of guideline databases, Medline and Embase. Then, six independent reviewers evaluated the methodological quality using the tools “Appraisal of Guidelines for Research and Evaluation” (AGREE II) and “Recommendation EXcellence” (AGREE-REX). The Kruskal–Wallis (H) test was used to explore differences among subgroups and Spearman’s correlation to examine the relationship between individual domains. Three guidelines developed by consortia from Canada, Germany and the United Kingdom were eligible for the evaluation. The German guideline achieved the highest scores, fulfilling 65 to 92% of the criteria in AGREE II and 67 to 84% in AGREE-REX, whereas the Canadian guideline scored 31 to 71% of the criteria in AGREE II and 33 to 46% in AGREE-REX. The domains “stakeholder involvement“ and “values and preferences“ were identified as methodological weaknesses requiring particular attention and improvement in future guideline efforts.
CRIS-Team Scopus Importer:2021-04-02
Keywords: actinic keratosis; AGREE; Level of evidence; Practice guideline; Solar keratosis

A Systematic Review and Meta-Analysis of Interventions for Actinic Keratosis from Post-Marketing Surveillance Trials - Steeb, Theresa; Wessely, Anja; Harla, Matthias; Heppt, Franz; Koch, Elias; Leiter, Ulrike; Garbe, Claus; Schöffski, Oliver; Berking, Carola; Heppt, Markus (Journal of Clinical Medicine, 2020)
Multiple interventions are available for the treatment of actinic keratosis (AK) showing high efficacy in pivotal trials. However, data from post-marketing surveillance studies have received little attention until now. Here, we systematically investigate interventions for AK from post-marketing surveillance trials as a proxy for real-world efficacy and tolerability. A systematic literature search was conducted in Medline, Embase, and CENTRAL. Pertinent trial registers were hand-searched until 25 March 2020. Results were pooled using a random-effects model to calculate pooled proportions and relative risks (RR) or were described qualitatively. Eleven records with a total sample size ofn= 4109 were included. Three of the studies had an active-controlled design, while seven were single-armed. Participant complete clearance ranged from 23.1% for diclofenac sodium 3% gel to 88.9% for ingenol mebutate 0.05% gel. The lesion-specific clearance rate for photodynamic therapy (PDT) was 74% (95% confidence interval (CI) 56-87%). The recurrence rate was significantly higher for diclofenac sodium 3% in comparison to imiquimod 5% cream (RR 1.10, 95% CI 1.02-1.1.8) and ranged from 10.6% for ingenol mebutate 0.015% gel to 23.5% for PDT. Few patients discontinued the trials due to adverse events. The results from the majority of the post-marketing surveillance studies deviated from those of pivotal trials.
CRIS-Team WoS Importer:2020-08-21

Cash is king: the balance of costs and effectiveness of treatments for actinic keratosis - Steeb, Theresa; Heppt, Franz; Berking, Carola (British Journal of Dermatology, 2020)
CRIS-Team Scopus Importer:2020-04-17

Fumaric Acid Esters and TNF alpha Inhibitors - Do they affect the Fertility of male Patients with Psoriasis? - Heppt, Franz; Colsmann, A.; Maronna, A.; Uslu, Ugur; Heppt, M.; Kiesewetter, Franklin; Sticherling, Michael (2017)
EVALuna2:34352

Hydradenitis suppurativa - new exploration on the famous Disease - Oetterich, Kerstin; Heppt, Franz; Sticherling, Michael (2017)
EVALuna2:34354

Influence of TNF-alpha inhibitors and fumaric acid esters on male fertility in psoriasis patients - Heppt, Franz; Colsman, A.; Maronna, A.; Uslu, Ugur; Heppt, M. V.; Kiesewetter, Franklin; Sticherling, Michael (Journal of the European Academy of Dermatology and Venereology, 2017)
OBJECTIVE: Is there any influence of a therapy with TNF-alpha inhibitors or fumaric acid esters and of disease activity status on male fertility and sperm quality in patients with psoriasis? METHODS: In this monocentric, open-label, prospective study, semen samples were collected from patients receiving either TNF-alpha inhibitors or fumaric acid esters for moderate-to-severe plaque psoriasis. Semen was analysed at baseline before onset of the systemic therapy and monitored every 3 months under therapy. Sperm parameters were assessed according to the current WHO definitions. RESULTS: In total, 101 semen specimens from 27 patients were obtained. Mean Psoriasis Area and Severity Index (PASI) score at baseline was 11.05. Only 14.8% of patients showed a normozoospermia without any other abnormal seminal values. 85.2% of patients had at least one sperm/seminal abnormality, including two patients showing an azoospermia. Interestingly, 48.1% showed sperm parameters indicative of genital tract inflammation. Therapy with TNF-alpha inhibitors or fumaric acid esters did not have any negative effects on relevant sperm parameters such as mean total sperm number, sperm concentration, total and progressive motility. No major gonadal dysfunction was observed in any patient. CONCLUSION: At baseline, many patients with psoriasis showed abnormal semen/sperm parameters and remarkably elevated leukocytes and values of seminal polymorphonuclear elastase, indicating a genital tract inflammation. Thus, genital tract inflammation may represent an important comorbidity of psoriasis, little attention paid to so far. Regarding treatment with TNF-alpha inhibitors or fumaric acid esters, no major negative (side-) effects on sperm quality were observed.
EVALuna2:34337

Interventions for Actinic Keratosis in Nonscalp and Nonface Localizations: Results from a Systematic Review with Network Meta-Analysis - Steeb, Theresa; Wessely, Anja; Schmitz, Lutz; Heppt, Franz; Kirchberger, Michael; Berking, Carola; Heppt, Markus (Journal of Investigative Dermatology, 2020)
Myriad interventions are available for the treatment of actinic keratosis located on the face or scalp. However, lesions located outside the head and neck have received little attention until now. We aimed to synthesize the current knowledge of interventions for actinic keratosis in nonscalp and nonface localizations. Randomized controlled trials reporting data for these localizations were searched in MEDLINE, Embase, and The Cochrane Library CENTRAL, as well as in pertinent trial registers until 25 March 2020. A total of 13 randomized controlled trials with 1,380 patients were included in a systematic review. Five treatment modalities were evaluated and compared with placebo in a frequentist network meta-analysis, including cryosurgery, ingenol mebutate, photodynamic therapy, colchicine, and 5-fluorouracil. In the network meta-analysis, cryosurgery showed the highest participant complete clearance rates (risk ratio, 7.73; 95% confidence interval = 3.21–18.61; 10 studies; I2 = 20.3%; Grading of Recommendations Assessment, Development, and Evaluation, ++–) and lesion clearance rates (risk ratio, 2.97; 95% confidence interval = 2.45–3.59; 4 studies; I2 = 0%; Grading of Recommendations Assessment, Development, and Evaluation, ++–) compared with placebo. Ingenol mebutate demonstrated the highest participant partial clearance rates compared with placebo (risk ratio, 7.12; 95% confidence interval = 4.36–11.64; 5 studies; I2 = 0%; Grading of Recommendations Assessment, Development, and Evaluation, +++-). The mean reduction of lesions and occurrence of adverse events was poorly reported. The certainty of the evidence varied from very low to high and was limited by imprecision and study limitations.
CRIS-Team Scopus Importer:2020-08-07

Patients Receiving Cytokine Inhibitors Have Low Prevalence of SARS-CoV-2 Infection - Simon, David; Tascilar, Koray; Krönke, Gerhard; Kleyer, Arnd; Zaiss, Mario; Heppt, Franz; Meder, Christine; Atreya, Raja; Klenske, Entcho; Dietrich, Peter; Abdullah, Abdullah; Kliem, Thorsten; et al. (ARTHRITIS & RHEUMATOLOGY, 2020)
CRIS-Team WoS Importer:2021-01-15

Patients with immune-mediated inflammatory diseases receiving cytokine inhibitors have low prevalence of SARS-CoV-2 seroconversion - Simon, David; Tascilar, Koray; Krönke, Gerhard; Kleyer, Arnd; Zaiss, Mario; Heppt, Franz; Meder, Christine; Atreya, Raja; Klenske, Entcho; Dietrich, Peter; Abdullah, Abdullah; Kliem, Thorsten; et al. (Nature Communications, 2020)
Immune-mediated inflammatory diseases (IMIDs) of the joints, gut and skin are treated with inhibitors of inflammatory cytokines. These cytokines are involved in the pathogenesis of coronavirus disease 2019 (COVID-19). Investigating anti-SARS-CoV-2 antibody responses in IMIDs we observe a reduced incidence of SARS-CoV-2 seroconversion in IMID patients treated with cytokine inhibitors compared to patients receiving no such inhibitors and two healthy control populations, despite similar social exposure. Hence, cytokine inhibitors seem to at least partially protect from SARS-CoV-2 infection.
CRIS-Team Scopus Importer:2020-08-07

Psoriasis as a Manifestation of an Immune Reconstitution in Two Patients with Hepatitis C Treated with Ledipasvir/Sofosbuvir - Heppt, Franz; Sticherling, Michael (Acta Dermato-Venereologica, 2017)
EVALuna2:34349

Psoriasis in children: a single center analysis - Heppt, Franz; Raap, J.; Sticherling, Michael (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2019)
CRIS-Team WoS Importer:2019-05-17

Psoriasis in children: a single-centre analysis - Heppt, Franz; Raap, J.; Sticherling, Michael (2017)
EVALuna2:34339

Psoriasis vulgaris as Manifestation of Immune Reconstitution in Patients with Hepatitis C under Treatment with Ledipasvir/Sofosbuvir - Heppt, Franz; Sticherling, Michael (2017)
EVALuna2:34350

Secondary syphilis infection under treatment with ustekinumab - Uslu, Ugur; Heppt, Franz; Sticherling, Michael (Clinical and Experimental Dermatology, 2017)
EVALuna2:34342

Sinus Pericranii - Heppt, Franz; Meder, Christine; Wagner, Nicola (Deutsches Ärzteblatt international, 2020)
CRIS-Team WoS Importer:2020-05-05

Sister-Mary-Joseph-Knoten der Brust – Beschreibung einer neuen Entität? - Popp, Judith; Heppt, Markus; Berking, Carola; Heppt, Franz (Journal der Deutschen Dermatologischen Gesellschaft, 2021)
CRIS-Team Scopus Importer:2021-04-23

Skin and Soft Tissue Infections Caused by Mycobacterium chelonae: More Common Than Expected? - Uslu, Ugur; Boehm, Olga; Heppt, Franz; Sticherling, Michael (Acta Dermato-Venereologica, 2019)
Mycobacterium chelonae is a rapidly growing non-tuberculous mycobacterium, which causes infections of the human skin and soft tissue. Despite an increasing incidence of such infections, patients are often misdiagnosed. We report here 5 patients with cutaneous and/or soft tissue infection due to M. chelonae who were diagnosed and treated at our centre. Two of the 5 patients were on immunosuppressive treatment. While clinical presentations differed in each patient, all had a long history of skin lesions. In addition to careful history-taking, tissue biopsies were obtained for mycobacterial culture and histopathological examination. Culture-directed antibiotic therapy was initiated, which resulted in a slow, but continuous, healing of the lesions. In summary, M. chelonae infections are still relatively rare, but should be considered in both immunocompromised and immunocompetent patients with prolonged skin lesions resistant to standard antibiotic treatment. For diagnosis, tissue analysis for mycobacterial culture and histopathological examination, and once diagnosed, adequate antibiotic treatment, is needed.
CRIS-Team WoS Importer:2019-09-10

Stereotactic radiation therapy for liver metastases: factors affecting local control and survival. - Andratschke, Nicolaus H. J.; Nieder, Carsten; Heppt, Franz; Molls, Michael; Zimmermann, Frank (Radiation Oncology, 2015)
To report on outcome and toxicity of stereotactic body radiotherapy (SBRT) for liver metastases in patients not eligible for surgery.From 2000 to 2009, 74 patients with 91 liver metastases from different primaries have been treated with SBRT at our institution. Median planning target volume was 123 ccm (range: 10.6-1074 ccm). Treatment consisted of 3-5 fractions with 5-12.5 Gy/ fraction prescribed to the surrounding 60-95% isodose with daily image guidance. Regular follow-up included CT or MRI imaging until tumor progression.Median local recurrence-free interval was 23 months with a local control rate of 74.7%, 48.3% and 48.3% after 1, 2 and 3 years. Only minimum biologically effective dose (BED) to gross tumor volume (GTV) remained as independent significant factor for local control in multivariate analysis. No local recurrences were observed in lesions (n = 12) which received a minimal BED to the GTV of 120 Gy. Including 26 local recurrences, 67 patients (91%) showed disease progression after SBRT with a median time of 5 months. Median overall survival was 27 months with survival rates of 77%, 30% and 27% at 1, 3 and 5 years. On multivariate analysis only GTV volume remained as independent significant prognostic factor for overall survival (p = 0.002). No grade 3 to 5 acute toxicity and no grade 4 or 5 late toxicity occurred.SBRT for liver metastases was well tolerated in this non-selected patient cohort and yielded good local control despite the considerable size of most lesions treated. Long-term survival is possible after SBRT.
EVALuna2:86702

Unilateral, intermittent, pulsating Swelling of the Forehead - Heppt, Franz; Meder, Christine; Wagner, N. (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2019)
CRIS-Team WoS Importer:2019-05-17

Where do we stand with immune checkpoint blockade for advanced cutaneous squamous cell carcinoma? A systematic review and critical appraisal of existing evidence - Steeb, Theresa; Wessely, A.; Heppt, Franz; Harlaß, M.; Berking, Carola; Heppt, Markus (British Journal of Dermatology, 2020)
Immune checkpoint blockade (ICB) has tremendously changed the field of oncological therapy. Recently, the PD-1-blocking antibody cemiplimab was approved by the FDA and the EMA for the treatment of advanced cutaneous squamous cell carcinoma (cSCC).1 However, clinical practice guidelines currently do not cover specific recommendations regarding the management of advanced cSCC with ICB. Hence, we have performed a systematic review on the current use of ICB for advanced cSCC.
EVALuna2:212852